Emotional atmosphere in third-graders’ mathematics classroom – an analysis of pupils’ drawings - Laine, Anu; Näveri, Liisa; Ahtee, Maija; Hannula, Markku S.; Pehkonen, Erkki (NOMAD Nordic Studies in Mathematics Education, 2012)
The aim of this study is to find out what kind of emotional atmosphere dominates in third-graders’ mathematics lessons. The analysis is based on pupils’ drawings. In total 133 drawings were analyzed by looking for content categories related to a holistic evaluation of emotional atmosphere during mathematics lesson. As a summary we can conclude that the emotional atmospheres in the mathematics lessons are mainly positive even though the differences between the classes are large. Furthermore, it can be said that asking pupils to do drawings is a good and many-sided method to collect data about the emotional atmosphere of a class.